The beginning of the early dynastic period at Ur - Benati, Giacomo (Iraq, 2014)
This article presents a reconsideration of the architecture, stratigraphy and finds from Building Level H, excavated in Trial Pit Fat Ur. Analysis of Woolley's original excavation records, kept at the British Museum, provides the basis for a contextual reconstruction. A new complete study of published and unpublished materials now housed at the British Museum and at the Penn Museum of Philadelphia is offered here. Distribution of in situ artefacts is examined here in order to provide insights on the function of the excavated loci. Finally, pottery and glyptic assemblages, considered from a regional perspective, are used to define the chronological horizon of Level H.